2010
DOI: 10.1590/s0103-50532010001200010
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of alumina nanoparticles with silane coupling agents

Abstract: No presente trabalho nós descrevemos a modificação da superfície de nanopartículas de alumina utilizando alcoxissilanos possuindo grupos epóxi (agentes de acoplamento baseados em silano, SCA). Os materiais foram caracterizados por espectroscopia de infravermelho e ressonância magnética nuclear de estado sólido. Considerando-se que as nanopartículas de alumina podem ser modificadas com SCA, como evidenciado por 13 C CPMAS RMN, a presença de grupos arilsulfonato na superfície da alumina promoveu a polimerização … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 15 publications
0
46
0
Order By: Relevance
“…Prado et al [92] treated the alumina NPs surface with [2-(3,4 epoxycyclohexyl)ethyl]trimethoxysilane (Fig. 16).…”
Section: Silanesmentioning
confidence: 99%
“…Prado et al [92] treated the alumina NPs surface with [2-(3,4 epoxycyclohexyl)ethyl]trimethoxysilane (Fig. 16).…”
Section: Silanesmentioning
confidence: 99%
“…The surface modification decreased the thermal stability of alumina, in comparison with pristine alumina NPs. 16 The surface of Al 2 O 3 NPs was modified using vinyltrimethoxysilane (VTMS) layer. Analyses revealed that the silane coupling successfully adsorbed on the surface of nano Al 2 O 3 via chemical interaction.…”
Section: Introductionmentioning
confidence: 99%
“…1. OIM slides were firstly aminated by incubation in 1% APTMS diluted with H 2 O for 1.5 h at room temperature, (20,24) washed in H 2 O for 10 min, and then dried in an oven for 10 min at 110 °C. All experiments reported in this section were performed at room temperature.…”
Section: Immobilization Of a Probe Dnamentioning
confidence: 99%